2020
DOI: 10.1089/bfm.2020.29157.hmj
|View full text |Cite
|
Sign up to set email alerts
|

ABM Clinical Protocol #34: Breast Cancer and Breastfeeding

Abstract: A central goal of The Academy of Breastfeeding Medicine is the development of clinical protocols for managing common medical problems that may impact breastfeeding success. These protocols serve only as guidelines for the care of breastfeeding mothers and infants and do not delineate an exclusive course of treatment or serve as standards of medical care. Variations in treatment may be appropriate according to the needs of an individual patient. Background B reast cancer is the most common malignancy in women w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 33 publications
1
3
0
6
Order By: Relevance
“…It has been suggested that women receiving chemotherapy experience difficulties in initiating breastfeeding because of decreased milk production. 43 Our data support this suggestion as only three of the six women who initiated breastfeeding after receiving chemotherapy during their pregnancy continued to breastfeed their babies at discharge. We did not collect postneonatal follow‐up data to determine whether breastfeeding after chemotherapy had any adverse impacts.…”
Section: Discussionsupporting
confidence: 68%
“…It has been suggested that women receiving chemotherapy experience difficulties in initiating breastfeeding because of decreased milk production. 43 Our data support this suggestion as only three of the six women who initiated breastfeeding after receiving chemotherapy during their pregnancy continued to breastfeed their babies at discharge. We did not collect postneonatal follow‐up data to determine whether breastfeeding after chemotherapy had any adverse impacts.…”
Section: Discussionsupporting
confidence: 68%
“…В случае проведения РТ или частичной мастэктомии выработка молока снижена в той груди, где было проведено лечение [15]. Это связано с тем, что в результате лечения происходят необратимые изменения тканей железы, включая фиброз, атрофию и дольковый склероз [16].…”
Section: лактацияunclassified
“…Reduction in risk for breast and ovarian cancer is among the benefits of breastfeeding. Specialists who follow-up pregnant and lactating cancer survivors should be aware of the close monitoring necessary throughout this period [ 126 ]. Healthcare providers need to reassure women that breastfeeding has not proved to increase the risk of relapse.…”
Section: Malignancies and Breastfeedingmentioning
confidence: 99%
“…Galactagogues are often phytoestrogens in a concentrated form, which could promote oncogenesis or decrease the efficacy of hormonal therapy [ 127 ]. Domperidone and other drugs inducing prolactin release may be contraindicated due to an increased risk of breast cancer development with elevated prolactin [ 126 , 128 ].…”
Section: Malignancies and Breastfeedingmentioning
confidence: 99%